2019
DOI: 10.1038/s41598-018-38133-x
|View full text |Cite|
|
Sign up to set email alerts
|

New microhylid frog genus from Peninsular India with Southeast Asian affinity suggests multiple Cenozoic biotic exchanges between India and Eurasia

Abstract: Anurans in Peninsular India exhibit close biogeographical links with Gondwana as well as Laurasia, often explainable by the geological history of the Indian subcontinent; its breakup from Gondwanan landmasses followed by long isolation that resulted in diversification of endemic lineages, and subsequent land connections with Asia that enabled dispersal of widespread groups. Although widely distributed, the frog subfamily Microhylinae mostly comprises of geographically restricted genera found either in Southeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 62 publications
7
65
1
Order By: Relevance
“…The tectonic collision between the Indian subcontinent (ISC) and the Eurasian landmass during the Early Cenozoic is widely recognized as a key event that caused significant geologic and climatic changes, such as the rise of the Himalaya, uplift of the Tibetan plateau, and a general drying of Central Asia ( Harrison et al, 1992 ; An et al, 2001 ; Guo et al, 2002 ; Molnar, 2005 ; Solovyeva et al, 2018 ). This tectonic event also induced a major biotic interchange between the ISC and Eurasia and is widely regarded as a major driver of biotic diversification ( Wilkinson et al, 2002 ; Roelants, Jiang & Bossuyt, 2004 ; Li et al, 2013 ; Garg & Biju, 2019 ). Numerous studies have demonstrated that floral and faunal elements reached and colonized tropical Asia from Gondwanaland via the northward drifting ISC ( Dayanandan et al, 1999 ; Klaus et al, 2010 , 2016 ; Kamei et al, 2012 ; Morley, 2018 ), the so called “out-of-India” hypothesis ( Bossuyt & Milinkovitch, 2001 ; Conti et al, 2002 ; Gower et al, 2002 ; Biju & Bossuyt, 2003 ; Sparks, 2003 ; Dutta et al, 2004 ; Karanth, 2006 ; Datta-Roy & Karanth, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tectonic collision between the Indian subcontinent (ISC) and the Eurasian landmass during the Early Cenozoic is widely recognized as a key event that caused significant geologic and climatic changes, such as the rise of the Himalaya, uplift of the Tibetan plateau, and a general drying of Central Asia ( Harrison et al, 1992 ; An et al, 2001 ; Guo et al, 2002 ; Molnar, 2005 ; Solovyeva et al, 2018 ). This tectonic event also induced a major biotic interchange between the ISC and Eurasia and is widely regarded as a major driver of biotic diversification ( Wilkinson et al, 2002 ; Roelants, Jiang & Bossuyt, 2004 ; Li et al, 2013 ; Garg & Biju, 2019 ). Numerous studies have demonstrated that floral and faunal elements reached and colonized tropical Asia from Gondwanaland via the northward drifting ISC ( Dayanandan et al, 1999 ; Klaus et al, 2010 , 2016 ; Kamei et al, 2012 ; Morley, 2018 ), the so called “out-of-India” hypothesis ( Bossuyt & Milinkovitch, 2001 ; Conti et al, 2002 ; Gower et al, 2002 ; Biju & Bossuyt, 2003 ; Sparks, 2003 ; Dutta et al, 2004 ; Karanth, 2006 ; Datta-Roy & Karanth, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that floral and faunal elements reached and colonized tropical Asia from Gondwanaland via the northward drifting ISC ( Dayanandan et al, 1999 ; Klaus et al, 2010 , 2016 ; Kamei et al, 2012 ; Morley, 2018 ), the so called “out-of-India” hypothesis ( Bossuyt & Milinkovitch, 2001 ; Conti et al, 2002 ; Gower et al, 2002 ; Biju & Bossuyt, 2003 ; Sparks, 2003 ; Dutta et al, 2004 ; Karanth, 2006 ; Datta-Roy & Karanth, 2009 ). At the same time, a set of phylogenetic studies of different animal groups proposed an alternative “out-of-Eurasia” biogeographic hypothesis, suggesting a Southeast Asian origin of these lineages with further dispersal and colonization of the ISC during its collision with the Eurasian landmass ( Raxworthy, Forstner & Nussbaum, 2002 ; Renner, 2004 ; Köhler & Glaubrecht, 2007 ; Van der Meijden et al, 2007 ; Macey et al, 2008 ; Grismer et al, 2016 ; Garg & Biju, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The endemic Madagascan Mantellidae with an Asian ancestry dispersed from Asia to Madagascar using India as a 'stepping stone' around 62.4 Ma ago. More recently, Garg and Biju (2019) showed that, the endemic microhylid frogs from the Western Ghats having affinities with Southeast Asian forms used two land bridges, one at about ~45.1 Ma and the second one around ~39.7 Ma, to colonize Southeast Asia. These dispersal events, interspersed with brief period of isolation, testify to periodic faunal interchanges between India and Asia prior to and during the suturing of these two landmasses.…”
Section: Figure 5 Palaeogeographic Models Proposed In the Past To Exmentioning
confidence: 99%
“…Among microhylids, the specimen is attributable to the microhyline Kaloula pulchra due to the combination of the following characters (compare Figs. 1 E, F and 1 G, H): Snoutvent length of 50-60 mm (the specimen is quite contorted and it is difficult to make a precise measurement) congruent with the size interval reported for adult males of this species, 54-72 mm, vs. smaller SVL in adult males of Adelastinae, Chaperininae, Hoplophryninae, Melanobatrachinae, and most species of Asterophryinae, Cophylinae, Gastrophryninae, and Scaphiophryninae); robust body; head wider than long with truncated snout (vs. acute, subtriangular in Gastrophryninae, Kalophryninae and Otophryninae); tympanic membrane absent; supratympanic fold present; absence of maxillary, premaxillary, and vomerine teeth (vs. presence of teeth in Dyscophinae and most nonminute Cophylinae); two palatal folds; proportionally small hindlimbs; presence of a spade-like inner metatarsal tubercle; finger tips not expanded (vs. greatly expanded in many members of Asterophryinae, Cophylinae, Scaphiophryninae and Phrynomerinae); dark brown, smooth dorsal skin with light paired lateral bands; darkly-pigmented single subgular vocal sac (Parker, 1934;Inger, 1966;Zweifel, 1986;Glaw & Vences, 2007;Du Preez & Carruthers, 2009;Rittmeyer et al, 2012;Zug, 2015;Vassilieva et al, 2016;Garg & Biju, 2019).…”
Section: The Specimenmentioning
confidence: 99%